NOVAS VEREDAS PARA A FORMAÇÃO DO PROFESSOR: LER PARA APRENDER A PESQUISAR - CORREA, ROSANEA MARIA MAZZINI (2018)
The intensive use of the Internet in Brazilian society raised transformations in the communicative behaviors, expanded access to information and brought into the current scenario discussions about the new reading and writing practices. Readings for research purpose, previously restricted to printed sources, has diversified with the electronic digital devices, contributing to the knowledge access. It is in this context that this study emerges, which objectives include: the reflection around the knowledge needed by the teacher to use the technologies in the literacy process; the analysis and comparison of the procedures used by the students to read for search on the Internet and printed sources and the observation of the exploratory reading of the texts before deciding what read and query. This qualitative research involves five educators and six students from the 4th year of the Interdisciplinary Cycle of Elementary School in a public school of the city's municipal of São Paulo. For data collection, the professionals were submitted to interviews, answered a questionnaire to build a profile and observed the classes at the computer lab of the school. In addition, students were interviewed and conducted to read activities on the Internet, and then in books and magazines in order to map their reading procedures, digging the challenges they face to read for research, and evaluate if the interest in the technologies influences in the way they interact with research in the digital environment. To provide a theoretical basis for this research, we have used the studies by Chartier (1998); Coscarelli (2016); Chartier (1998); Ferreiro and Teberosky (1991); Ferreiro (2001, 2002 and 2013); Gatti and Nunes (2009); Gatti (2010, 2014a and 2014b); Imbernón (2006); Kleiman (1998, 2001 and 2018); Lerner (2002); Nóvoa (2009); Perelman (2011); Goldin, Kriscautzky and Perelman (2012); Pischetola (2016); Rojo (2009), Rojo and Barbosa (2017); Rojo and Moura (2016); and Xavier (2015 and 2016). Data analysis reveals that the problems faced by students in reading in the digital environment are similar to those they encounter in books and magazines. They do not use suitable criteria to select sources; they find difficult to understand the texts and to seek the desired information. They also do not use the exploratory reading to consider what to read or consult, and they carry out to the full reading of all the inquired results. However, the domain of the technical mechanisms, the expedite and the facility to obtain the information, as well as the seduction by the multimodal texts interfere in a positive relationship with the activity to search for information on the Internet.